The Cultivable Bacteria Colonizing Canine Vagina During Proestrus and Estrus: A Large-Scale Retrospective Study of Influencing Factors - Sabine Schäfer-Somi; Dominik Lechner; Alexander Tichy; Joachim Spergser (Animals)
Background: The evaluation of canine vaginal bacteria during proestrus and estrus and the chosen parameters will help to prevent the misuse of antibiotics in veterinary medicine. Methods: This study carried out a retrospective analysis to obtain microbiological examination results for vaginal swabs from 696 healthy dogs, all of whom were patients from one clinic. Age, body weight, fur length (long or short hair), the time of sampling of vaginal swabs, the duration of proestrus/estrus, progesterone (P4) concentration (the first and last samples), and bacteriological findings were evaluated. Results: Only 3.7% (26/696) of the samples were negative for bacteria. The impact of fur length was low. However, the calculation of the odds ratios revealed that the chance for a high-grade growth of Escherichia (E.) coli and Mycoplasma (M.) canis increases with body weight class. The earlier the sampling was performed, the lower the number of high-grade cultures (p < 0.01). The duration between the first and last measurement of progesterone (P4) was positively related to the cultural detection of Pasteurellaceae, Streptococcus spp., and Enterococcus spp. (p < 0.05) and negatively to the cultivation of Mycoplasma spp. (p < 0.01). Conclusions: Our findings reflect some likely factors contributing to the variability of the physiological vaginal flora in dogs, which may help interpret cultured bacteriological findings.